ASSOCIATION OF ANEMIA WITH PARASITIC INFESTATION IN PREGNANT NEPALESE WOMEN: RESULTS FROM A HOSPITAL-BASED STUDY DONE IN EASTERN NEPAL - Shah, Binay Kumar; Baig, Lubna A. (Journal of Ayub Medical College Abbottabad, 2005)
Background: Anemia is a major contributor to maternal deaths in developing countries. Association of anaemia with helminthic infestations has been seen in the world and by eliminating it, anemia may be reduced with positive effects on maternal outcome. Methodology: A comparative cross-sectional study was done to assess the association of anemia with parasitic infestation, and other significant risk factors in eastern Nepal. One hundred and twelve pregnant women with and without anemia were enrolled in the study at the antenatal clinic at Dhankuta District Hospital, Nepal from May 2001 to July 2001. The data on social and demographic variables was collected through a structured questionnaire. Hemoglobin estimation and stool examination for parasitic infestation was done for all these women. Results: Anemia was found in 66 (58.9%) women and 52 (46.5%) had helminthic infestation. Anemia was significantly related to hookworm infestation. There was a highly significant relationship between education and the knowledge of women regarding effect of helminthic infestations (P<0.000), transmission and spread of infestations (P<0.000). The knowledge of women regarding effect of helminthic infestation was significantly (P<0.001) related to the occurrence of parasitic infestations but its association with anaemia was not significant. Conclusion: Hookworm infestation in pregnancy was significantly related with anaemia. Hence all women coming to antenatal clinics should be screened for hookworm infestation. The antenatal care should include de-worming with correction and prevention of anaemia. Key Words: hookworm infestation, anaemia, pregnancy